2003
DOI: 10.1021/es034600k
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Dechlorination of Polychlorinated Biphenyls:  Threshold Concentration and Dechlorination Kinetics of Individual Congeners in Aroclor 1248

Abstract: Reductive dechlorination of individual PCB congeners in Aroclor 1248 was investigated using sediment microorganisms from the St. Lawrence River (NY). No dechlorination was observed at Aroclor concentrations below 40 ppm [137 nmol (g of sediment)(-1)]. Above this threshold, congeners could be divided into three categories: group A, congeners that dechlorinated above 40 ppm; group B, congeners that dechlorinated only at high concentrations above 60 ppm [206 nmol (g of sediment)(-1)]; and group C, lower chlorinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 23 publications
7
50
1
2
Order By: Relevance
“…The average scaling If the two factors were separated, as anticipated, the lower concentration samples would be unique to one source contribution (Figure 7) and the higher concentration samples to the other source contribution. This separation is expected because samples with low PCB concentrations are unable to sustain a sufficient population of microbial dechlorinating organisms, while high-concentration samples are (Sokol et al, 1994;Cho et al, 2003). This is not the case here however, as both plots mainly have the highest contributions from the same samples (Figure 7).…”
Section: Pcbs In the Sheboygan River Sedimentsmentioning
confidence: 82%
“…The average scaling If the two factors were separated, as anticipated, the lower concentration samples would be unique to one source contribution (Figure 7) and the higher concentration samples to the other source contribution. This separation is expected because samples with low PCB concentrations are unable to sustain a sufficient population of microbial dechlorinating organisms, while high-concentration samples are (Sokol et al, 1994;Cho et al, 2003). This is not the case here however, as both plots mainly have the highest contributions from the same samples (Figure 7).…”
Section: Pcbs In the Sheboygan River Sedimentsmentioning
confidence: 82%
“…They observed a threshold for dechlorination at concentrations at about 35 to 45 mg/kg, with reactions not occurring below those concentrations. Similarly, Cho et al (2003) found PCB congeners in St. Lawrence River sediment slurries that were dechlorinated only if initially present at concentrations above 40 mg/kg, others that were dechlorinated at concentrations above 60 mg/kg, and less chlorinated congeners that increased in concentration. [However, it is remarkable that final concentrations of congeners were significantly lower than threshold values (Cho et al (2003).]…”
Section: Biotransformation Mechanismsmentioning
confidence: 95%
“…Similarly, Cho et al (2003) found PCB congeners in St. Lawrence River sediment slurries that were dechlorinated only if initially present at concentrations above 40 mg/kg, others that were dechlorinated at concentrations above 60 mg/kg, and less chlorinated congeners that increased in concentration. [However, it is remarkable that final concentrations of congeners were significantly lower than threshold values (Cho et al (2003).] Based on a larger group of studies, reviews of PCB biotransformation have estimated this possible general threshold at 50 mg/kg (Tiedje et al 1993), but one ofthese reviews suggests that dehalogenation might continue at lower PCB concentrations if cometabolism is involved and food for dehalogenating organisms is available.…”
Section: Biotransformation Mechanismsmentioning
confidence: 95%
“…Co-eluting peaks were indicated as multiple congeners. Total chlorines per biphenyl was calculated as the product of the average number of chlorines and molar concentration of each congener divided by the sum of the total molar concentration of all congeners (Cho et al 2003). When co-eluting peaks were different homologs, equal amounts of each homolog were assumed ).…”
Section: Mesocosm Experimentsmentioning
confidence: 99%
“…In sediment microcosms from the Saint Lawrence River spiked with Aroclor 1242, Cho et al (2003) reported threshold concentrations of 35 to 45 mg/kg PCB, below which PCB dechlorination ceased. Fish (1996) found that the maximum dechlorination rate of spiked Aroclor 1242 in sediment microcosms over a range of concentrations from 10 to 250 mg PCBs/kg increased with increasing initial concentration.…”
Section: Introductionmentioning
confidence: 99%